First Report in Cuba: Lasiodiplodia pseudotheobromae as Causal Agent of Dieback in Murraya Paniculata (L.) Jacq. (Rutaceae) - Cabrera, Reinaldo I; Manzano, Ana Maria; Herrera, Sara; Toledo, Yoandy; Crespo, Karina L; Sanchez-Yanez, Juan Manuel (Scientific Modelling and Research, 2022)
In Cuba and in other parts of the world, Murraya paniculata is an ornamental plant as well as agricultural crops of economic value that has presented chlorotic leaves, defoliation and regressive death, which suggests that it is a phytopathogenic fungus. The objective of this work was to demonstrate that the attack of this phytopathogenic agent is due to Lasiodiplodia pseudotheobromae, responsible for the regressive death in M. paniculata. In this sense, an investigation was carried out at the laboratory level of isolation and identification of the fungus based on the fact that DNA was extracted to ensure the correct identity of this genus and species of fungus that was cultivated with a commercial kit that supports a fungal attack of L. pseudotheobromae as a causal agent of regressive death in M. paniculata, with the help of the consulted literature. This is the first report found of this fungal disease caused by L. pseudotheobroame. This finding is important due to the risk of attacking other non-ornamental plants, as well as agricultural crops that affect agricultural production on the island of Cuba, to avoid a phytosanitary problem of greater impact if it is considered that the COVID-19 pandemic 19 caused other economic problems related to agriculture on the island.